Perspectives of older patients on the qualities which define a "good family nurse": A qualitative study - Ludmila Marcinowicz; Ewa Taranta (Wiley, 2020)
Abstract Aim To explore what the term "good family nurse" means to older patients. Design A descriptive qualitative study design was used, and a purposive sampling method was adopted. Methods Semi‐structured interviews were conducted with 21 patients aged 65 years and older who were receiving primary care in Bialystok (Poland). The interviews were recorded and then transcribed in verbatim. The data were analysed using content analysis. Data were collected between February 2017 and December 2018. Results We identified six main categories of qualities that define a "good family nurse". These are as follows: (a) personal traits and attributes (sex and individual characteristics and behaviours not directly related to nursing); (b) providing care (caring attitude and patient support); (c) communicating with the patient (the ability to listen and inform the patient); (d) professional competence (knowledge, professional experience and good technical skills); (e) ethical attitude (respect, patience and vocation); and (f) availability (the frequency and duration of home visits, organization of the doctor's appointments).